2008
DOI: 10.1007/s10875-008-9176-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Immune Deficiency Disorders Presenting as Autoimmune Diseases: IPEX and APECED

Abstract: Reviewing recent advances in our understanding of the small subgroup of PIDD patients with defined causes for autoimmunity may lead to the development of more effective treatment strategies for idiopathic human autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 76 publications
0
77
0
5
Order By: Relevance
“…Studies have shown an association between immunodeficiency syndromes in childhood and the later development of autoimmune disorders (32). IgA deficiency, the most common primary immunodeficiency with a prevalence of 1 per 500-700 among Europeans, is associated with both systemic and organspecific autoimmune diseases (33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an association between immunodeficiency syndromes in childhood and the later development of autoimmune disorders (32). IgA deficiency, the most common primary immunodeficiency with a prevalence of 1 per 500-700 among Europeans, is associated with both systemic and organspecific autoimmune diseases (33).…”
Section: Discussionmentioning
confidence: 99%
“…En effet, des souris invalidées, ou présentant des mutations de STAT5, présentent un déficit en lymphocytes Treg qui est associé à une auto-immunité [12]. L'existence des cellules Treg a également été montrée chez l'homme [13,14] et des mutations dans le gène de FoxP3 entraînent l'absence de ces cellules et un syndrome auto-immun sévère (syndrome d'immunodérégulation, polyendocrinopathie, enté-ropathie auto-immune liée au chromosome X, ou IPEX) [15]. Le rôle du système IL-2 dans le développement des cellules Treg a été fortement suggéré par plusieurs études montrant que des patients, porteurs de mutations touchant le gène de l'IL-2Rα (CD25) et chez lesquels le récepteur CD25 n'est pas exprimé, présentent des désordres immunitaires semblables à ceux observés chez les souris, dont des manifestations auto-immunes, une lymphadénopathie et des infections virales persistantes [16].…”
Section: (➜)unclassified
“…As an example, T1D represents a major component of the IPEX (immune dysfunction, polyendocrinopathy, enteropathy, X-linked) syndrome [1][2][3] that affects patients with abrogated Treg cell function due to mutations in the FOXP3 gene [4][5][6]. Studies have been performed in adult non-obese diabetes (NOD) mice with transgenic expression of the β-cellreactive BDC2.5 T cell receptor (TCR) on CD4 + T cells and the human diphtheria toxin receptor (DTR) selectively in Foxp3 + Treg cells.…”
Section: Introductionmentioning
confidence: 99%